Designing a Training Model for Value-Creating School Principals in Secondary School - Maleki, Azam; Soleimanpouromran, Mahboubeh; Afrasiabi, Roya (International Journal of Education and Cognitive Sciences, 2022)
Purpose: The objective of this study was to design a comprehensive training model for developing value-creating school principals in secondary education. Methods and Materials: The research employed a mixed-methods approach, combining qualitative and quantitative methodologies. The qualitative phase involved thematic analysis of semi-structured interviews with educational experts and a review of relevant literature to identify essential competencies. The quantitative phase included a survey of 321 secondary school principals from North Khorasan Province, selected using simple random sampling. Data were analyzed using structural equation modeling (SEM) with SPSS 24 and LISREL software to validate the identified competencies and develop the training model. Findings: The study identified three critical dimensions for developing value-creating school principals: individual, social, and organizational competencies. Within these dimensions, key competencies such as the "spirit of seeking success," "creating an entrepreneurial attitude in parents and educators," and "organizational self-confidence" were highlighted as essential for effective school leadership. The findings suggest that while all identified competencies are important, those related to personal motivation, social engagement, and organizational innovation have the most significant impact on a principal's ability to create value in their schools. Conclusion: The study provides a robust framework for the development of training programs aimed at cultivating value-creating school principals. By focusing on the identified individual, social, and organizational competencies, training programs can better prepare principals to lead effectively and drive educational excellence. The study also highlights the need for ongoing research and practice to further refine these competencies and adapt them to different educational contexts.